Are Brownfield Concessions Poised for a Comeback? New Signs of Life After a Decade in Decline - Leigland, James (World Bank, Washington, DC, 2012)
Once expected to be the signature contract of private participation in infrastructure and for a time its fastest growing form, the brown field concession was hit hard by the Asian crisis and has never recovered. Because these contracts involve existing, usually dilapidated government assets, brown field concessions tackled the toughest infrastructure problems in the developing world. But the Asian crisis exposed the fragility of this mechanism, and its sudden unpopularity almost single-handedly crashed the developing world market for private participation in infrastructure.